Vancomycin-resistant Enterococcus – a study on its prevalence from different clinical samples in a rural medical college hospital - Sayani Bose; Rituparna De; Paulami Palchowdhury; Anirban Bhaduri (Asian Journal of Medical Sciences, 2025)
Background: Vancomycin-resistant Enterococcus (VRE) is an important cause of nosocomial infection with Enterococcus faecium causing most of the VRE infections. Widespread use of glycopeptides in health care facilities has led to the development of VRE and enterococcal infections with high-level resistance to aminoglycosides, beta-lactamase production and glycopeptide (including vancomycin) resistance are difficult to treat and often pose a therapeutic challenge to health care facilities. Aims and Objectives: This study aimed to determine the antibiotic susceptibility pattern of Enterococcus species from various clinical specimens and to find out the occurrence rate of vancomycin-resistant enterococci. Materials and Methods: This study was conducted at the Department of Microbiology of Tamralipto Government Medical College and Hospital, East Midnapore, West Bengal. A total of 688 clinical samples were the total sample size taken. Isolation and identification of Enterococcus spp. were done by standard microbiological procedures such as culture, Gram staining, and suitable biochemical tests were conducted. Antibiotic susceptibility testing was done by the Kirby–Bauers disc diffusion method on Mueller–Hinton agar and results were interpreted according to Clinical and Laboratory Standards Institute (CLSI) guidelines 2023. Teicoplanin sensitivity was performed for those isolates showing resistance to vancomycin. For strains showing resistance to vancomycin by the Kirby–Bauers disc diffusion method, vancomycin minimum inhibitory concentrations (MIC) were performed by E-test (Hi media) with MIC breakpoints between 4 and 32 as per CLSI criteria. This was compared with the control strain of American Type Culture Collection Enterococcus faecalis 29212 as per CLSI 2023 guidelines. Results: A total of 48 Enterococcus isolates were obtained from 688 clinical samples; 31 (8.05%) were detected from 385 urine samples, 9 (6.72%) were detected from 134 blood samples, 5 (5.15%) were detected from 97 pus/wound swab, and 3 (4.17%) were detected from 72 bronchoalveolar lavage fluid samples. Among the 48 Enterococcus isolates, 13 (27.08%) were vancomycin-resistant out of which nine were E. faecalis and four were E. faecium. Enterococcus species showed maximum resistance toward ciprofloxacin followed by ampicillin and maximum sensitivity toward teicoplanin and linezolid. Conclusion: Implementation of strict infection control measures, antimicrobial policies, and proper surveillance are required to identify, contain, and treat VRE infections to reduce mortality and morbidity.